Why do consumers remain financially illiterate? The empirical test of some less investigated reasons - Oratowski, Piotr; Cwynar, Andrzej; Cwynar, Wiktor; Dankiewicz, Robert; Ostrowska-Dankiewicz, Anna (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
Although financial literacy becomes increasingly important in more and more financialised world, and despite broad-based financial education interventions, consumers still display large shortcomings in the literacy. In this study, using multivariate linear regression and a nationally representative sample of adult Poles (N=1,067), we test some little-studied potential determinants of financial literacy with the purpose to further explain low financial literacy levels. We found that respondents who are more interested in financial domain, have less difficulty in understanding information supplied by means of numbers, and report more learning from own mistakes are at the same time more financially literate, even after controlling for sociodemographic characteristics. Possible implications regarding the role of these factors for financial education are discussed.